Students' Knowledge in Science: An Evaluation via Hydroponic Kit. - Shaharuddin, Wan Yusoff Wan; Hashim, Hartini; Abas, Muhamad Azahar; Hassin, Nor Hizami; Karim, Muhammad Firdaus Abdul; Hussin, Hamzah; Amin, Mohamad Faiz Mohd; Hamzah, Zulhazman; Amir, Aainaa; Idris, Nor Shahirul Umirah; Halim, Nurul Syazana Abdul; Sulaiman, Nursufiah; et al. (Pertanika Journal of Social Sciences & Humanities, 2022)
Every year, high school students response to choosing a science stream has indicated a declining pattern. It may be due to the lack of technical application of science that students cannot foresee, thus preventing them from having a clear vision of how science and technology could greatly help daily human life. The study aims to assess the knowledge of high school students through STEM education via a project-based learning method using the hydroponic kit. Seventy students from a government school in Kota Bharu, Kelantan, Malaysia, participated in this study. The questionnaire was then evaluated based on the scores and displayed improvement. The mean score for the pretest of general knowledge was M=3.8857, SD=1.41977, and then it increased to M=6.1857, SD=1.21932 for the post-test. In addition, the mean score for the pretest of hydroponic system advantages was M=6.2000, SD=1.93068, which increased to M=8.8286, SD=0.65875 for the post-test. Meanwhile, the mean score for the pre-test of disadvantages of the hydroponic system was M=7.2571, SD=2.21121, subsequently increasing to M=9.4286, SD=0.73369 for the post-test. Finally, the mean score for the pre-test of practical knowledge was M=9.3429, SD=2.51307, and then increased to M=15.0571, SD=1.84065 for the post-test. Students' responses to the tests indicated that their interest in the field of science has increased through their involvement in the hydroponic kit project.